A case of musical anhedonia due to right putaminal hemorrhage: a disconnection syndrome between the auditory cortex and insula. Issue 6 (1st November 2016) - Satoh, Masayuki; Kato, Natsuko; Tabei, Ken-ichi; Nakano, Chizuru; Abe, Makiko; Fujita, Risa; Kida, Hirotaka; Tomimoto, Hidekazu; Kondo, Kiyohiko
ABSTRACT: A 63-year-old, right-handed professional chorus conductor developed right putaminal hemorrhage, and became unable to experience emotion while listening to music. Two years later, neurological examination revealed slight left hemiparesis. Neuromusicological assessments revealed impaired judgment of "musical sense, " and the inability to discriminate the sound of chords in pure intervals from those in equal temperament. Brain MRI and tractography identified the old hemorrhagic lesion in the right putamen and impaired fiber connectivity between the right insula and superior temporal lobe. These findings suggest that musical anhedonia might be caused by a disconnection between the insula and auditory cortex.